Subjectivity, literature and testimonial poetry: the voices of childhood in contexts of armed conflict in Colombia - Suárez Galvis, Viviana (Universidad Distrital Francisco José de Caldas, 2021)
This article presents a state of the art about the memories that literature and testimonial poetics have built on childhoods in ecologies characterized by political violence and armed conflict. The balance carried out shows how the understanding of the conditions in which boys and girls configure their subjectivities constitutes a problem of interest that questions the relationships between the categories of subject, politics and culture with important challenges for the field of education. education in Colombia. In addition, literature and testimonial poetry are aesthetic-cultural expressions that allow not only to activate individual and collective memories, but also to transform educational settings through a new horizon of significance in which feelings constrained by the harshness of war emerge.